Rozpad Československa (Czech Journal of International Relations, 2000)
Eric Stein: Czecho/Slovakia - Ethnic Conflict, Constitutional Fissurre, Negotiated Breakup. Ann Arbor,The University of Michigan Press 1997, 407 stran, ISBN 0-472-10804-2.